The influence of B doping on phase formation and microstructural evolution in NHL during solid-state reactions - Yanbo Zhang; Zhiyuan Xu; Conghao Shao; Hongmei Qin; Ze Liu; Dongmin Wang (Case Studies in Construction Materials, 2024)
Natural Hydraulic Lime (NHL), was synthesized by doping B2O3 into calcium carbonate and silica aerogel. By introducing varying levels of B3+ ion doping (0/1/5/10/15/20/25 mol%), a range of NHL compositions were successfully prepared, thereby enabling regulation of the NHL phase composition. Furthermore, through the doping of 25 mol% B3+ ions, in-depth investigations employing XRD, SEM, and FT-IR were conducted to explore phase transitions and ion migration during NHL calcination at different temperatures. Thermal analysis kinetics studies further revealed the variation of activation energies for CaCO3 decomposition and C2S crystallization with changing levels of B3+ ion doping. The introduction of B ions was observed to stabilize the α’ phase of dicalcium silicate (C2S) and moderately enhance the reactivity of calcium oxide (CaO). B3+ ions significantly influenced the crystallization mechanism of C2S, shifting it from a diffusion-controlled process to a heterogeneous nucleation process. The application of the Kissinger and Flynn-Wall-Ozawa (FWO) methods assisted in elucidating the underlying reasons for these differences. Both approaches demonstrated a substantial decrease in activation energy, signifying the pronounced influence of B doping on the sintering regime and phase transition mechanism of NHL. In summary, the precise modulation of NHL phase composition and sintering regime was achieved through B doping. These findings not only deepen our understanding of the mechanistic role of B3+ ions in NHL preparation and application but also offer robust guidance for the production process of NHL.